Advanced Experimental Technique for Radiation Damage Effects in Nuclear Waste Forms: Neutron Total Scattering Analysis. (19th February 2018) - Lang, Maik; O'Quinn, Eric C.; Shamblin, Jacob; Neuefeind, Jörg
ABSTRACT: For the past 30 years, the development of durable materials for radionuclide immobilization has been driven by efforts to dispose of wastes generated by the nuclear fuel cycle [National Research Council, 'Waste Forms Technology and Performance: Final Report', the National Academies Press, Washington D.C., 2011]. Many materials have been developed, but there still exist large gaps in the knowledge of fundamental modes of waste form degradation in repository environments. An important aspect of waste form science is the behavior of the materials under intense irradiation from decaying actinides and fission products. This irradiation induces a wide range of defects and disorder, the details of which depend on the specific waste form material. At the present time, it is not fully explained how radiation effects will influence the performance of nuclear waste forms and their long-term retention of fission products and actinides under operational conditions. The complex defect behavior and radiation damage must be understood over a range of length scales, from the initial atomic-scale defect structure to the long-range observable material modification. This is particularly challenging and requires advanced characterization techniques. This contribution describes how pair distribution function (PDF) analysis obtained from neutron total scattering experiments can be applied in the research field of waste form science to uniquely characterize radiation effects in a wide range of materials, including crystalline complex oxides and waste glasses. Neutron scattering strength does not have an explicit Z-dependence; this allows access to many low-Z elements, such as oxygen, that cannot be accurately studied with X-rays. In many cases, this can permit a detailed analysis of both cation (often high-Z) and anion (often low-Z) defect behavior. In contrast to traditional crystallography, which relies on long-range order, PDF analysis probes the local defect structure, including changes in site occupation, coordination, and bond distance. This is particularly important when characterizing aperiodic waste glasses with no long-range order at all. In contrast to X-ray characterization which requires very little sample mass (∼0.1 mg), neutron characterization (even at state-of-the-art spallation facilities) requires relatively large sample mass (∼50 - 100 mg). Obtaining this quantity is challenging for studies of irradiated materials, but by tailoring our experimental approach to use high-energy ions (GeV) with very high penetration depth, we are able to produce the required mass.